Control of the acoustical and visual concepts in education - Schafroth, Theodore (My University, 1977)
The purpose of this study had three general aims. First, in controlling the acoustical concepts in education, it was possible to show that auditory abilities and discrimination were enhanced because of better information transfer. Second, that visual discrimination and perception are key factors in the general subject of visual literacy. Third, the visual and auditory areas reinforce each other in many ways but work against each other in others. This was a library research study. Current books, latest periodicals both in print and microfilmed, and Doctoral Abstracts were the chief sources in the chosen field. It was the desire of the writer to confine the results as being applied to normal school conditions, conditions that nearly all teachers would encounter in a normal teaching career. It was found that auditory distractions of various kinds are detrimental to the learning process. One of these distractions, reverberation, is controlled by various construction and arrangement methods. It was found that visual discrimination and visual perception were dependent upon the perceptual system of the individual. In the school room the proper amount and control of light will enhance the system. The visual and the auditory areas reinforce each other in many ways but may work against each other. There is a tendency to favor one system over the other under certain conditions. Verbal coding may be supplemented or replaced by visual imagery. Effective visual design and presentation are functions of many interrelationships.
Keywords: Visual learning.; Visual perception.; Noise control.; Auditory perception in children.